Molecular characterization and in silico evaluation of surfactins produced by endophytic bacteria from Phanera splendens - de Souza, Eleane Monaliza de Cerqueira; de Oliveira, Maycon Vinicius Damasceno; Siqueira, José Edson de Sousa; Rocha, Daniela Cristiane da Cruz; Marinho, Anderson do Nonato Rosario; Marinho, Andrey Moacir do Rosario; Marinho, Patrícia Santana Barbosa; Lima, Anderson H. (Frontiers in Chemistry, 2023)
The Phanera splendens (Kunth) Vaz. is a medicinal plant that is used in traditional medicine for the treatment of various diseases, such as malaria. This plant presents highly efficient endophytic bacterial isolates with biocontrol properties. Bacillus sp. is responsible for the production of a variety of non-ribosomal synthesized cyclic lipopeptides which highlight the surfactins. Surfactins have a wide range of antimicrobial activity, including antiplasmodial activity. There is scientific evidence that surfactin structure 2d-01 can be a potent inhibitor against a Plasmodium falciparum sirtuin (Sir2) by acting on the Sir2A protein as the target. The Pf genome encodes two known sirtuins, PfSir2A and PfSir2B, where PfSir2A is a regulator of asexual growth and var gene expression. Herein, we have identified six surfactins produced by endophytic bacteria and performed in silico analysis to elucidate the binding mode of surfactins at the active site of the PfSir2A enzyme. Among the characterized surfactins, 1d-02 showed the highest affinity for the PfSir2A enzyme, with binding energy values equal to -45.08 ± 6.0 and -11.95 ± 0.8 kcal/mol, using MM/GBSA and SIE methods, respectively. We hope that the information about the surfactin structures obtained in this work, as well as the potential binding affinity with an important enzyme from P. falciparum, could contribute to the design of new compounds with antimalarial activity.